Pendidikan Karakter: Media Buku Cerita Bergmbar Berbasis Wayang Sukuraga untuk Meningkatkan Pemahaman Konsep dalam Materi Tanggung Jawab pada Mata Pelajaran Pendidikan Pancasila : Penelitian - Atot Sugiri; Yoesrina Novia Vini Syafitri (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to develop an instructional media in the form of a picture storybook based on Wayang Sukuraga to instill the value of responsibility in elementary school students through Pancasila Education. The research employed the Research and Development (R&D) method using the ADDIE development model, which includes Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects were third-grade students from SDN Cigalasar and SDN Cikadu. Observations revealed that students struggled to understand and apply the value of responsibility, and the existing learning media were neither engaging nor contextual. The developed media was validated by content, media, and language experts, with a result categorized as